2002
DOI: 10.1128/jvi.76.11.5612-5626.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-Independent Activation of the Epstein-Barr Virus Lytic Cycle

Abstract: The protein kinase C (PKC) pathway has been considered to be essential for activation of latent EpsteinBarr virus (EBV) into the lytic cycle. The phorbol ester tetradecanoyl phorbol acetate (TPA), a PKC agonist, is one of the best understood activators of EBV lytic replication. Zp, the promoter of the EBV immediate-early gene BZLF1, whose product, ZEBRA, drives the lytic cycle, contains several phorbol ester response elements. We investigated the role of the PKC pathway in lytic cycle activation in prototype c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 58 publications
4
85
0
Order By: Relevance
“…For herpesviruses, the ability to induce replication depends on not only the type of CMR but also the type of cell line being induced (Gradoville et al, 2002). The lack of persistently infected cell lines does not help attempts to isolate CFPHV, so we tried to get around this problem by using early subculture cells known to contain CFPHV pol DNA.…”
Section: Discussionmentioning
confidence: 99%
“…For herpesviruses, the ability to induce replication depends on not only the type of CMR but also the type of cell line being induced (Gradoville et al, 2002). The lack of persistently infected cell lines does not help attempts to isolate CFPHV, so we tried to get around this problem by using early subculture cells known to contain CFPHV pol DNA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that latently infected LCL can be driven to enter into the lytic phase of the EBV life cycle by exposure to PMA, a protein kinase C agonist, and sodium butyrate (NaB), a histone deacetylase inhibitor (Bhaduri-McIntosh & Miller, 2006;Gradoville et al, 2002), so protein lysates were prepared from LCL that were either treated with PMA þ NaB or left untreated. In three out of four animals tested, a higher frequency of LCV-specific cells was detected when lysate from PMA/NaBtreated LCL was used as the source of LCV antigen (Figure 2a).…”
Section: Optimization Of the Lcv Antigen Used In The Ifn-c Elispot Assaymentioning
confidence: 99%
“…The presence of LCV genome and protein expression of LCV latent and lytic phase proteins were confirmed (refer to supplemental data section for additional details). Lysates were prepared from non-treated LCL or LCL treated with 20 ng phorbol-12-myristate 13-acetate (PMA)/ml (Sigma, St. Louis, MO) þ 3 mM sodium butyrate (NaB) (Sigma) for 72 h to enhance LCV gene expression (Gradoville et al, 2002). Lot-specific titers for use in the IFN-g ELISPOT assay were determined from dose-response curves; both LCV seronegative and seropositive PBMC were routinely tested to ensure specificity of responses.…”
Section: Antigensmentioning
confidence: 99%
“…The inducing effect of phorbol esters is mediated through protein kinase C (PKC) (Davies et al, 1991), and also primarily requires the ZI and ZII binding motifs in the BZLF1 promoter , although the intermediary factors are not well defined. However, PKC activation is not required for induction of lytic EBV by certain stimuli (Gradoville et al, 2002). Activation of the BRLF1 (Rp) promoter requires EGR-1 and Sp1 binding sites (Zalani et al, 1992(Zalani et al, , 1995.…”
Section: Induction Of Lytic Ebv Infectionmentioning
confidence: 99%